Greenlandic qajaq as heritage, activity and tourism - Lennert, Frederik Adam (UiT The Arctic University of Norway, 2015)
I will be using the Greenlandic name to what you know, as “kayak” which for me will be qajaq. (Note on Inuit terms: The word “kayak” is the English equivalent for a word spoken by Native Inuit. The word is made with the tongue against the uvula to produce a “q” sound (instead of a “k”). The “a” sounds are pronounced like the “a” in “father”. The word for Inuit watercraft should be spelled “qayaq” in English, or “qajaq” in Danish or German). My late grandfather was raised to become a hunter and qajaq man; he was born in 1910 in Oqaatsut. Until the end of 1920´s all the boys were raised to become hunters, they learned to balance sitting on their parents labs, while their parents sing the hunting and paddling songs. But then modern times and the fishing were introduced in the 1930´s, which made the qajaq more and more invisible through the years. Until the early 1980´s Manasse Mathæussen and Thimothæus Poulsen revitalized the interest for the qajaq, since then every town started their own qajaq union. In 1985 the country organization came to birth. With so much cultural heritage the tourism industry is more or less ignoring it. So I asked why the qajaq was so little used within tourism? The answer was: it is too dangerous. I used qualitative interview with the local qajaq men and tour operators, where I found out that it is not dangerous, you just need to specify your demands for your clients. Meanwhile Visit Greenland is marketing Greenland with the Big Arctic Five, where four of the five can be experienced in other Arctic countries. This thesis will and should open eyes for the local as well as the National marketers in Greenland. Just by using cultural and heritage you can reach pioneers, as the qajaq has done –it´s a worldwide recreation watercraft. Key words: Cultural heritage, cultural heritage tourism qajaq.